2020
DOI: 10.1002/jcad.12315
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of the Medicare Coverage Gap on Counseling Professionals: Results of a National Study

Abstract: The authors surveyed 6,550 members of the American Counseling Association regarding the current impact of Medicare policy on counseling professionals. More than half of respondents (54.8%) had been directly affected by Medicare reimbursement barriers, including 70.0% of practicing counselors. Statistical analyses indicated significant associations between years in the profession, direct experience with the Medicare coverage gap, and participation in professional advocacy related to Medicare. Implications for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Master's students may not have yet experienced the negative consequences associated with Medicare ineligibility. An interesting finding of our related study (Fullen et al, 2020) was that practicing counselors were far more likely to have direct experience of the Medicare coverage gap, and that discrepancy may directly influence participation in the legislative advocacy process.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Master's students may not have yet experienced the negative consequences associated with Medicare ineligibility. An interesting finding of our related study (Fullen et al, 2020) was that practicing counselors were far more likely to have direct experience of the Medicare coverage gap, and that discrepancy may directly influence participation in the legislative advocacy process.…”
Section: Discussionmentioning
confidence: 83%
“…This information was used to identify any major differences between our sample and the total population of ACA members. Slight differences are noted in Fullen et al (2020). We used frequency counts to identify which professional issues were receiving the most advocacy attention, as well as which methods were being used to engage in MRA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, members of our team used a survey of ACA members (described in the Procedure section) to establish baseline data intended to quantify and describe the current effects of Medicare provider policy, or what has been described as the Medicare mental health coverage gap (MMHCG; Fullen, Lawson, & Sharma, ). We found that 70% of practicing counselors surveyed had been directly affected by the MMHCG, including 50.3% who had turned away or referred a new client, 38.8% who had been forced to prematurely cease treatment with an existing client who became Medicare eligible, and 39.9% who had used pro bono or sliding scale approaches to maintain their work with those insured by Medicare.…”
mentioning
confidence: 81%
“…We found that 70% of practicing counselors surveyed had been directly affected by the MMHCG, including 50.3% who had turned away or referred a new client, 38.8% who had been forced to prematurely cease treatment with an existing client who became Medicare eligible, and 39.9% who had used pro bono or sliding scale approaches to maintain their work with those insured by Medicare. We also found data suggesting that practicing counselors are increasingly likely to experience problems due to the MMHCG the longer they remain in the field and that ACA members who experienced the direct impact of the MMHCG were significantly more likely to participate in Medicare‐related advocacy, including efforts to contact lawmakers to inform them about the impact of this policy on Medicare beneficiaries (Fullen et al, ). These findings suggest that the scope of the MMHCG is more prevalent than previously understood.…”
mentioning
confidence: 99%